Pengaruh Penggunaan Artificial Intelligence terhadap Kecerdasan Intelektual Mahasiswa PAI Universitas Islam Zainul Hasan Genggong Probolinggo - Utari, Herliana; Quthny, Abu Yazid Adnan; Arobi, Ibnul (Jurnal Simki Pedagogia, 2024)
Education is experiencing rapid development in the increasingly advanced digital era. Artificial intelligence can create a more personalized and adaptive learning system, help teachers create more effective learning content, and help students understand lecture material. Apart from that, artificial intelligence also helps in the educational administration and management process. The use of AI has a positive impact on increasing students' intellectual intelligence in completing coursework. Students can utilize artificial intelligence to get more effective assistance in understanding and carrying out academic assignments. This investigation seeks to ascertain how the application of artificial intelligence affects the intellectual intelligence of PAI students at Zainul Hasan Genggong Islamic University in Probolinggo. Using a population of 87 students from the 2020 Islamic Religious Education Study Program (PAI), this research used associative quantitative methodology. Because the population is less than 100, this research uses a census sampling method, namely all students are sampled. A questionnaire was used to collect data, and SPSS 25 edition programming was used to carry out normality tests and simple linear regression analysis. The results of the analysis show that for the 2020 class of PAI Zainul Hasan Genggong Islamic University Probolinggo students, the application of AI had an influence on intellectual intelligence by 57.1%, and the remaining 42.9% was influenced by other factors. Therefore, the use of artificial intelligence has a significant influence on the intellectual intelligence of PAI students at Zainul Hasan Genggong Islamic University, Probolinggo.